Circulating FABP4 Is a Prognostic Biomarker in Patients With Acute Coronary Syndrome but Not in Asymptomatic Individuals. Issue 8 (August 2015) - Reiser, Hans; Klingenberg, Roland; Hof, Danielle; Cooksley-Decasper, Seraina; Fuchs, Nina; Akhmedov, Alexander; Zoller, Stefan; Marques-Vidal, Pedro; Marti Soler, Helena; Heg, Dik; Landmesser, Ulf; Rodondi, Nicolas; et al.
Abstract : Objective—: Blood-borne biomarkers reflecting atherosclerotic plaque burden have great potential to improve clinical management of atherosclerotic coronary artery disease and acute coronary syndrome (ACS). Approach and Results—: Using data integration from gene expression profiling of coronary thrombi versus peripheral blood mononuclear cells and proteomic analysis of atherosclerotic plaque–derived secretomes versus healthy tissue secretomes, we identified fatty acid–binding protein 4 (FABP4) as a biomarker candidate for coronary artery disease. Its diagnostic and prognostic performance was validated in 3 different clinical settings: (1) in a cross-sectional cohort of patients with stable coronary artery disease, ACS, and healthy individuals (n=820), (2) in a nested case–control cohort of patients with ACS with 30-day follow-up (n=200), and (3) in a population-based nested case–control cohort of asymptomatic individuals with 5-year follow-up (n=414). Circulating FABP4 was marginally higher in patients with ST-segment–elevation myocardial infarction (24.9 ng/mL) compared with controls (23.4 ng/mL; P =0.01). However, elevated FABP4 was associated with adverse secondary cerebrovascular or cardiovascular events during 30-day follow-up after index ACS, independent of age, sex, renal function, and body mass index (odds ratio, 1.7; 95% confidence interval, 1.1–2.5; P =0.02). Circulating FABP4 predicted adverse events with similar prognostic performance as the GRACE in-hospital risk score or N-terminal pro–brain natriuretic peptide. Finally, no significant difference between baseline FABP4 was found in asymptomatic individuals with or without coronary events during 5-year follow-up. Conclusions—: Circulating FABP4 may prove useful as a prognostic biomarker in risk stratification of patients with ACS. Abstract : Supplemental Digital Content is available in the text.